2015
DOI: 10.1063/1.4919792
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent thermal properties of single-walled carbon nanotube thin films

Abstract: We herein report the determination of the intrinsic thermal conductivity (κ) and interfacial thermal conductance (g) of single-walled carbon nanotube thin films (50 nm) on top of a SiO2 substrate. The study was performed as a function of temperature (300–450 K) using the opto-thermal technique. The value of κ decreases nonlinearly by approximately 60% from a value of 26 Wm−1 K−1 at 300 K to a value of 9 Wm−1 K−1 at 450 K. This effect stems from the increase of multi-phonon scattering at higher temperatures. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
1
24
2
1
Order By: Relevance
“…Examinations of thermal conductivity of SWCNT film and determination of the temperature for which it reaches the maximum value were performed by Duzynska and Zdrojek et al [72][73][74]. They obtained an SWCNT film and then examined the impact of elevated temperature on changes in thermal conductivity using Raman spectroscopy.…”
Section: Impact Of Temperaturementioning
confidence: 99%
“…Examinations of thermal conductivity of SWCNT film and determination of the temperature for which it reaches the maximum value were performed by Duzynska and Zdrojek et al [72][73][74]. They obtained an SWCNT film and then examined the impact of elevated temperature on changes in thermal conductivity using Raman spectroscopy.…”
Section: Impact Of Temperaturementioning
confidence: 99%
“…Raman spectroscopy was used to assess the sheet thermal conductance of each film [31,32]. Originally, this method was applied to the determination of the thermal conductivity of graphene, although the thermal conductivities of SWNT films have been determined with similar techniques [20,33]. In this method, the thermal resistance of the film is calculated as…”
Section: Measurement Of the Thermal Transport Propertiesmentioning
confidence: 99%
“…However, it has also been reported that the thermal conductivity of individual SWNTs vary with length [8][9][10][11], diameter [12,13], chirality [14,15], and defects [16]. The thermal conductivities of vertically aligned SWNT films [17][18][19], and random-network SWNT films [20,21], have been shown to range from 1 to 100 W / m K. It is known that the thermal conductivity of SWNT ensembles such as these can be affected by phonon scattering [22][23][24], bundle structure [25], contact thermal resistance among the SWNTs [26] and other factors. Thus, in these ensembles of SWNTs, the superior thermal transport properties of individual SWNTs are not fully realized.…”
Section: Introductionmentioning
confidence: 99%
“…We chose thin films made of single-walled carbon nanotubes because we can easily exclude effects "D" and "F." Moreover, the nanotube films were fabricated in such a manner that they are loosely bound to the glass substrate, which excludes effect "C" and strengthens effect "E." Another important advantage of thin films made of single-walled carbon nanotubes is their discrete nature, which immediately implies indelible structural inhomogeneity at the nanoscale, handling of which we are especially interested in this paper. The literature shows the richness of the work on the influence of temperature on physical properties of various sp 2 carbon materials like graphene or carbon nanotubes; [32,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] however, the current knowledge on the role of temperature in Raman studies is still not complete. This is because there is still the lack of full understanding of which exactly phenomena are grasped or observed during the Raman experiments involving temperature, [57] the lack of the uncertainty assessment, which makes it impossible to assign proper weights to measured data and to their differences, [65] and, the most important, the lack of the estimation of the variability of the reported values within the investigated samples.…”
Section: Introductionmentioning
confidence: 99%